Micro-level structural change decomposition of carbon productivity : Application to electricity generation in Finland - Kuosmanen, Natalia; Kuosmanen, Timo; Maczulskij, Terhi (Elsevier, 2025)
The transition to renewable energy can lead to major structural changes within the energy sector: climate policies encourage the entry of cleaner producers while at the same time driving polluting firms out of the market. However, previous macro-level structural decompositions of carbon intensity and carbon productivity fail to capture the underlying micro-level dynamics, such as firm entry and exit, industry switching, and the reallocation of emissions between firms. The purpose of this study is to fill this gap by presenting a novel micro-level structural change decomposition of carbon productivity. Using comprehensive firm-level register data of the greenhouse gas emissions in the Finnish electricity generation industry in 2000-2019, we find that more efficient allocation of carbon emissions across firms was the main driver of carbon productivity growth in Finnish electricity generation during the study period. We also find that structural change, especially the entry of new firms, played a significant role in the carbon productivity development of this industry.